1999
DOI: 10.1111/j.1528-1157.1999.tb01595.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Treatment of Children with Epilepsy with Valproate or Carbamazepine May Cause Subclinical Hypothyroidism

Abstract: Summary:Purpose: The aim of the study was to evaluate serum thyroid hormone balance in children receiving long-term therapy with carbamazepine (CBZ), valproate (VPA), and phenobarbital (PB).Methods: We determined serum levels of triiodothyronine (TJ, thyroxine (TJ, free thyroxine (FT,), thyroxine-binding globulin (TBC), and thyroid-stimulating hormone (TSH) in 148 healthy children and 141 children with epilepsy who had been receiving CBZ (61 patients), VPA (51 patients), or PB (29 patients) for 12-161 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 34 publications
9
88
1
1
Order By: Relevance
“…Several studies have been performed to observe the effect of VPA on thyroid and parathyroid functions; the results, however, have been controversial. Normal and abnormal levels of thyroid and parathyroid hormones (PH) have been reported in epileptic patients (Bentsen, Gram, & Veje 1983;Conran et al, 1985;Eiris-Punal et al, 1999;Isojarvi et al, 2001;Pena Grinan et al, 1991;Tanaka et al, 1987;Verrotti et al, 2001). In this study, we studied serum thyroid and PH levels in children with epilepsy who had been receiving long-term VPA therapy in order to determine whether there was any effect of VPA therapy on these hormones.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have been performed to observe the effect of VPA on thyroid and parathyroid functions; the results, however, have been controversial. Normal and abnormal levels of thyroid and parathyroid hormones (PH) have been reported in epileptic patients (Bentsen, Gram, & Veje 1983;Conran et al, 1985;Eiris-Punal et al, 1999;Isojarvi et al, 2001;Pena Grinan et al, 1991;Tanaka et al, 1987;Verrotti et al, 2001). In this study, we studied serum thyroid and PH levels in children with epilepsy who had been receiving long-term VPA therapy in order to determine whether there was any effect of VPA therapy on these hormones.…”
mentioning
confidence: 92%
“…Eiris-Punal et al (1999) recorded that mean T4, FT4, triiodothyronine (T3), and thyroid binding globulin levels were lower, and that mean TSH levels were higher in VPA-treated children than those of the control group. From these findings, they suggested that VPA might induce subclinical hypothyroidism (Eiris-Punal et al, 1999). Similarly, Bentsen et al (1983) noted that VPA caused a decrease in T4, FT4, and T3.…”
mentioning
confidence: 95%
“…Different thyroid dysfunctions have been reported in epileptic patients receiving VPA. In particular, reports on the effect of VPA on the thyroid hormones balance are conflicting, and both low and unchanged serum thyroxine (T 4 ) and free thyroxine (fT 4 ) levels have been found in patients receiving VPA monotherapy, never associated with overt thyroid dysfunction (9)(10)(11)(12)(13)(14): these studies showed normal mean TSH serum levels while other studies documented high TSH levels in patients receiving VPA therapy (10)(11)(12). However, the majority of studies have been performed in adult patients receiving these drugs, often in association with other AEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Cramer and Jones reported that fT4 levels were low in patients taking CBZ [23]. Eiris-Punal et al have reported low T4 and high TSH levels in patients taking CBZ and that subclinical hypothyroidism could develop in these patients [24]. Caksen et al reported that, although statistically not significant, long-term CBZ treatment caused a decrease in serum total and free T4 levels and that T4 levels returned to normal once the treatment was discontinued [25].…”
Section: Discussionmentioning
confidence: 99%